2023
DOI: 10.1186/s12967-023-04450-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FGFRs by pemigatinib induces G1 phase cell cycle arrest, cellular stress and upregulation of tumor suppressor microRNAs

Angelica Pace,
Fabio Scirocchi,
Chiara Napoletano
et al.

Abstract: Background Fibroblast growth factor receptor (FGFR) gene family alterations are found in several cancers, indicating their importance as potential therapeutic targets. The FGFR-tyrosine kinase inhibitor (TKI) pemigatinib has been introduced in the treatment of advanced cholangiocarcinoma and more recently for relapsed or refractory myeloid/lymphoid neoplasms with FGFR2 and FGFR1 rearrangements, respectively. Several clinical trials are currently investigating the possible combination of pemigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Currently, the circulating miRNAs are serving as potential molecular biomarkers for the diagnosis of lung cancer. Studies have shown that serum or plasma miRNAs are differentially expressed between lung cancer patients and healthy individuals, and circulating miRNAs in lung cancer can pass through the mitogen-activated protein kinase (MAPK) signaling pathway, fibroblast growth factor receptor (FGFR) signaling pathway, glucose transport cell apoptosis and antigen processing and presentation to play their related biological functions ( 15 ). Many miRNAs such as miR-17 and miR-19, miR-17, miR-20a, miR-18a, miR-92a-1, miR-19a, and miR-19b-1 participate in cancer-related processes ( 16 ).…”
Section: Lung Cancer and Mirnasmentioning
confidence: 99%
“…Currently, the circulating miRNAs are serving as potential molecular biomarkers for the diagnosis of lung cancer. Studies have shown that serum or plasma miRNAs are differentially expressed between lung cancer patients and healthy individuals, and circulating miRNAs in lung cancer can pass through the mitogen-activated protein kinase (MAPK) signaling pathway, fibroblast growth factor receptor (FGFR) signaling pathway, glucose transport cell apoptosis and antigen processing and presentation to play their related biological functions ( 15 ). Many miRNAs such as miR-17 and miR-19, miR-17, miR-20a, miR-18a, miR-92a-1, miR-19a, and miR-19b-1 participate in cancer-related processes ( 16 ).…”
Section: Lung Cancer and Mirnasmentioning
confidence: 99%